2019
DOI: 10.1177/2333794x19884826
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell and Neutrophil Counts and Response to Intravenous Immunoglobulin in Kawasaki Disease

Abstract: We explored parameters to predicting the efficacy of intravenous immunoglobulin (IVIG) therapy for patients with Kawasaki disease (KD). We retrospectively analyzed the laboratory data of 77 children with KD treated with IVIG. Data obtained before and within 24 hours after IVIG therapy were compared between responders and nonresponders. The white blood cell (WBC) and neutrophil counts were significantly lower in responders than nonresponders within 24 hours after IVIG. The areas under the receiver operating cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
(42 reference statements)
0
9
1
Order By: Relevance
“…Previous studies have suggested elevated neutrophil counts in IVIG resistance ( 17 , 18 , 71 ). However, we and others ( 72 , 73 ) did not observe elevated neutrophil counts in either IVIG-resistant patients or IVIG-resistant patients with CAL as compared to those in IVIG-responsive patients. Perhaps our small and heterogeneous patient population may account for these differences in the neutrophil counts.…”
Section: Discussioncontrasting
confidence: 76%
“…Previous studies have suggested elevated neutrophil counts in IVIG resistance ( 17 , 18 , 71 ). However, we and others ( 72 , 73 ) did not observe elevated neutrophil counts in either IVIG-resistant patients or IVIG-resistant patients with CAL as compared to those in IVIG-responsive patients. Perhaps our small and heterogeneous patient population may account for these differences in the neutrophil counts.…”
Section: Discussioncontrasting
confidence: 76%
“…Similar to adults with COVID-19, neutrophilia and lymphocytopenia are common in MIS-C. Neutrophils play a key functional role in Kawasaki disease with recent descriptions of NETosis and neutrophil activation in the form of CD11b and CD64 production ( 91 ). Neutrophil counts predict responsiveness of patients with Kawasaki disease to intravenous immunoglobulin therapy, also used in MIS-C ( 92 , 93 ). Neutrophils activation marker Fc γ receptor I (FcγRI; CD64) was described to be highly expressed on neutrophils of treatment-naive MIS-C patients in acute phase compared with healthy controls ( 94 ).…”
Section: Neutrophils and Covid-19 In Childrenmentioning
confidence: 99%
“…On the other hand, for predicting initial IVIG responsiveness, there have been reports on the utility of white blood cell count, hemoglobin, CRP, albumin, and d-dimer (32)(33)(34). However, we failed to predict the responsiveness of additional IVIG by those conventional markers as shown in Table 2.…”
Section: Discussionmentioning
confidence: 63%